Timeline of Multi-Organ Plasma Extravasation After Bleomycin-Induced Acute Lung Injury - Kitzerow, Oliver; Zucker, Irving H.; Lisco, Steven J.; Wang, Han-Jun (Frontiers in Physiology, 2022)
Acute lung injury (ALI) is characterized by the abrupt onset of clinically significant hypoxemia in the context of non-hydrostatic pulmonary edema. Acute lung injury is associated with cytokine release and plasma extravasation (PEx) that can cause pulmonary edema and subsequently acute respiratory distress syndrome (ARDS). Therefore, it is critical we understand the relationship between ALI and lung PEx. In addition, it is also important to assess PEx in the lungs and other organs post-ALI since ALI/ARDS often causes multi-organ failure. We hypothesized that ALI induces time-dependent lung PEx, which promotes extravasation in the heart, liver, kidney, spleen, pancreas, and gastrointestinal (GI) tract, in a time-dependent manner. To test our hypothesis, we administered bleomycin or saline via tracheal intubation in 8-week-old Sprague Dawley rats. At the terminal experiments, Evans Blue was injected (IV) through the femoral vein to allow for the visualization of PEx. Plasma extravasation of desired organs was evaluated at 3-, 7-, 14-, 21-, and 28-days after bleomycin or saline treatment by evaluating Evans Blue concentrations calorimetrically at fluorescence excitation wavelength of 620 nm (bandwidth 10 nm) and an emission wavelength of 680 nm (bandwidth 40 nm). Data show that ALI induces lung PEx beginning at day 3 and peaking between 7 and 21 days. Extravasation was also seen in all organs at varying degrees beginning at day 3 and peaking between days 7 and 14. Resolution appears to start after day 21 and continues past day 28. We conclude that ALI caused by bleomycin incites a time-dependent PEx of the lungs and multiple other organs.